A clinical prognostic scoring system for resectable gastric cancer to predict survival and benefit from paclitaxel- or oxaliplatin-based adjuvant chemotherapy - Qian J; Qian Y; Wang J; Gu B; Pei D; He S; Zhu F; Røe OD; Xu J; Liu L; Gu Y; Guo R; et al. (Dove Medical Press, 2016)
Jing Qian,1,* Yingying Qian,1,* Jian Wang,1 Bing Gu,2,3 Dong Pei,1 Shaohua He,1 Fang Zhu,1 Oluf Dimitri Røe,4–7 Jin Xu,8 Lianke Liu,1 Yanhong Gu,1 Renhua Guo,1 Yongmei Yin,1 Yongqian Shu,1 Xiaofeng Chen1 1Department of Oncology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, 2Department of Laboratory Medicine, The Affiliated Hospital of Xuzhou Medical College, 3Medical Technology Institute, Xuzhou Medical College, Xuzhou, People’s Republic of China; 4Department of Cancer Research and Molecular Medicine, Norwegian University of Science and Technology (NTNU), Trondheim, Norway; 5Department of Oncology, Clinical Cancer Research Center, 6Department of Clinical Medicine, Aalborg University Hospital, Aalborg, Denmark; 7Department of Surgery, Cancer Clinic, Levanger Hospital, Nord-Trøndelag Hospital Trust, Levanger, Norway; 8Department of Molecular Cell Biology and Toxicology, Jiangsu Key Lab of Cancer Biomarkers, Prevention & Treatment, Cancer Center, Nanjing Medical University, Nanjing, People’s Republic of China *These authors contributed equally to this work Background: Gastrectomy with D2 lymphadenectomy is a standard procedure of curative resection for gastric cancer (GC). The aim of this study was to develop a simple and reliable prognostic scoring system for GC treated with D2 gastrectomy combined with adjuvant chemotherapy.Methods: A prognostic scoring system was established based on clinical and laboratory data from 579 patients with localized GC without distant metastasis treated with D2 gastrectomy and adjuvant chemotherapy.Results: From the multivariate model for overall survival (OS), five factors were selected for the scoring system: ≥50% metastatic lymph node rate, positive lymphovascular invasion, pathologic TNM Stage II or III, ≥5 ng/mL preoperative carcinoembryonic antigen level, and <110 g/L preoperative hemoglobin. Two models were derived using different methods. Model A identified low- and high-risk patients for OS (P<0.001), while Model B differentiated low-, intermediate-, and high-risk patients for OS (P<0.001). Stage III patients in the low-risk group had higher survival probabilities than Stage II patients. Both Model A (area under the curve [AUC]: 0.74, 95% confidence interval [CI]: 0.69–0.78) and Model B (AUC: 0.79, 95% CI: 0.72–0.83) were better predictors compared with the pathologic TNM classification (AUC: 0.62, 95% CI: 0.59–0.71, P<0.001). Adjuvant paclitaxel- or oxaliplatin-based or triple chemotherapy showed significantly better outcomes in patients classified as high risk, but not in those with low and intermediate risk.Conclusion: A clinical three-tier prognostic risk scoring system was established to predict OS of GC treated with D2 gastrectomy and adjuvant chemotherapy. The potential advantage of this scoring system is that it can identify high-risk patients in Stage II or III who may benefit from paclitaxel- or oxaliplatin-based regimens. Prospective studies are needed to confirm these results before they are applied clinically. Keywords: gastric carcinoma, prognostic factor, TNM classification, paclitaxel, oxaliplatin